Improving services for glaucoma care in Nigeria: implications for policy and programmes to achieve universal health coverage. Issue 5 (15th February 2017) - Kyari, Fatima; Gilbert, Clare; Blanchet, Karl; Wormald, Richard
Abstract : Glaucoma in Africa is sometimes referred to as the silent thief of sight. In Nigeria, glaucoma is common, it is serious, ophthalmologists face many constraints in managing it, people do not even know they have it until it is advanced, patients do not understand or comply with treatment after they are diagnosed and the poor are more likely to be glaucoma blind. Available evidence indicates that the health system in Nigeria is failing to meet the needs of patients with glaucoma. Based on evidence, we propose future directions for improving services for glaucoma care in Nigeria, and the implications for policy and programmes to control glaucoma blindness, using a health system-oriented approach. Three complementary strategies are required: (i) strengthening clinical services for glaucoma—by developing models of glaucoma care, improving clinical treatment options, making medicines and equipment available, financing glaucoma care and training eye care workers; (ii) introducing initiatives for earlier detection of glaucoma in the clinic and approaches in the community and (iii) strengthening health system governance. Glaucoma is a complex disease to manage and addressing it as a public health problem is challenging. However, we need to change the paradigm to recognise that glaucoma is a potentially avoidable cause of blindness in Africa.